Peran Pembiayaan Mikro Syariah Bank BSI KCP Genteng Dalam Mendorong Pertumbuhan Ekonomi UMKM - Mustafidah, Wiwit; Tarhami, Alfin Farhan; Wafa, Ahmad Nur Izza (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
This research examines how effective micro-financing is at BSI KCP Genteng in promoting the growth of MSMEs in suburban regions. What makes this study unique is its focus on the important role that Islamic banking plays after mergers in reducing local capital obstacles. Utilizing a descriptive qualitative approach, data were collected through comprehensive interviews with branch management, marketing personnel, and MSME clients. Findings show that micro-financing plays a crucial role in enhancing working capital, increasing production capabilities, and broadening market opportunities. The discussion emphasizes that the role of this financial support goes beyond just providing funds; it acts as a strategic tool for fostering equitable economic well-being. This study suggests that Islamic financial institutions should adopt digital services and ongoing mentorship to reinforce MSMEs as the cornerstone of the local economy